On Moral Panic: Some Directions for Further Development. (March 2020) - Falkof, Nicky
This article is concerned with the continued salience of the notion of moral panic, an idea that has been both enormously influential in sociological and media research and has come under fire for various flaws. It reviews some of the most common critiques of moral panic, discussing why these are valid and where they fall short, and adds new comments on some weaknesses in the theory. It goes on to argue that the term and the idea of moral panic continue to have value as critical tools, but require updating. Suggested further developments include broadening moral panic to allow for analyses that consider the global south; taking account of the narrative layering that characterises these episodes; considering the intersection of moral panics and digital media; centralising fear and anxiety in moral panic research; considering moral panics as an interdisciplinary framework rather than as a strict model; and invoking a psychoanalytic rhetoric to further explain how moral panics work and what they do.